John Davis on Sports Sponsorship and Branding - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Marketing professor John Davis is director of the Centre for Marketing Excellence at the Lee Kong Chian School of Business, Singapore Management University. In his new book, The Olympic Games Effect, to be published by John Wiley in the run up to the Beijing Olympics, Davis examines why companies and even host cities and countries invest so heavily in sports sponsorship and branding. He also offers valuable lessons -- drawn from a rich collection of real-lfe examples -- on the risks involved, and how to maximise returns from these investments should businesses decide to go down this route.